Regulation of type III secretion system in Pseudomonas syringae - Xiao, Yanmei (Kansas State University, 2005)
P. syringae is a group of bacterial phytopathogens that can infect a wide variety of plants. These bacteria rely on the type III secretion system (TTSS) to deliver effectors into plant cells for infection. The TTSS genes, that encode the TTSS apparatus and the effectors, are repressed when bacteria grow in nutrient rich media but are strongly induced in the plants and in minimal medium (MM). Plant cutin monomers appear to negatively regulate the P. syringae TTSS genes. It is poorly understood how bacteria sense the environmental signals to regulate the TTSS genes. By genetic screen, four sets of transposon insertion mutants displaying aberrant TTSS gene expression were isolated: KB and fin mutants derepress the TTSS genes in rich medium KB and in the presence of a cutin monomer precursor in MM, respectively; min and pin mutants are defective in induction of TTSS genes in MM and in plants, respectively. A putative two-component sensor histidine kinase, RohS, is identified to be required for the induction of avrPto-LUC in MM and in plants. The rohS gene is in an operon containing a two-component response regulator gene rohR. Mutation of rohS in P. s. phaseolicola and P. s. tomato reduced the bacterial pathogenicity on hosts and HR-inducing activity on non-hosts. Our results suggested that RohS acts upstream of HrpR/HrpS. The phosphorylated RohR represses TTSS genes. It is likely that RohS acts as phosphatase of RohR in the TTSS-inducing conditions, and subsequently derepresses TTSS genes. Simple sugars such as glucose, sucrose and fructose are known to be inducers of the TTSS genes. Isolation of four min mutants defective in fructose-uptake enabled us to study if sugars serve as extracellular signals or as essential nutrients. Our results suggest that fructose acts as an essential nutrient for the activation of type III genes. These mutants slightly compromised induction of avrPto promoter in Arabidopsis and pathogenicity on the host bean plant, but displayed normal HR elicitation on non-host plant tobacco. The reduced pathogenicity suggested that exploitation of fructose from the host tissue is an important means for pathogenesis of P. s. phaseolicola.
Keywords: Type III secretion system; Pseudomonas syringae; Transposon mutagenesis; Agriculture, Plant Pathology (0480)